A Potret Motivasi Belajar dan Indeks Prestasi Kumulatif Mahasiswa Angkatan 2023 Fakultas Kedokteran Universitas Sam Ratulangi - Berhimpon, Siemona Lydia_Eunike; Pangemanan, Damajanty (Universitas Sam Ratulangi, 2024)
Abstract Background: Self-motivation plays an important role in the learning process and can affect the ups and downs of students academic achievements. Objective: This study aims to describe and describe the current conditions related to the motivation and academic achievements achieved by students of the Faculty of Medicine Class of 2023. Method: The data was sourced from the results of the Motivated Strategies for Learning Questionnaire (MSLQ) questionnaire and the report on the study results of PSPD, PSPDG, and PSIK students in semesters 1 and 2, which were then analyzed descriptively. Results: Students with high and moderate motivation obtained a GPA in the category with honors, in PSPD 86.8%, PSPDG 100%, and PSIK 98%. The majority of PSPD, PSPDG and PSIK students are female with high motivation and are currently obtaining a GPA in the category with honors, respectively 59.4%, 93.1% and 83.3%. PSPD, PSPDG and PSIK students aged 17-18 years have high motivation and are currently obtaining category GPA with honors of 83.3%, 79.3%, 93.13% respectively. PSPDG and PSIK students who came from North Sulawesi with moderate and high motivation obtained GPA scores with honors of 58.6% and 84.3% respectively, while PSPD students who came from outside North Sulawesi were 60.4%. Conclusion: study showed that PSPD, PSPDG, and PSIK students had high and moderate motivation, were female, and obtained a GPA in the category with honors. Then, PSPDG and PSIK students from North Sulawesi with medium and high motivation get GPA scores with honors, while PSPD students from outside North Sulawesi. Keywords: Motivation, Grade Point Average, Gender, Age, Origin Abstrak Latar Belakang: Motivasi diri berperan penting dalam proses pembelajaran dan dapat mempengaruhi naik turunnya indeks prestasi kumulatif (IPK) mahasiswa. Tujuan: Penelitian ini bertujuan untuk menggambarkan dan menguraikan kondisi terkini terkait motivasi dan prestasi akademik yang diraih oleh mahasiswa Fakultas Kedokteran Angkatan 2023. Metode: Data bersumber dari hasil kuesioner Motivated Strategies for Learning Questionnaire (MSLQ) dan laporan hasil studi mahasiswa PSPD, PSPDG, dan PSIK semester 1 dan 2, yang kemudian dianalisis secara deskriptif. Hasil: Mahasiswa dengan motivasi tinggi dan sedang dominan memperoleh IPK kategori dengan pujian, pada PSPD 86,8%, PSPDG 100%, dan PSIK 98%. Mahasiswa PSPD, PSPDG, dan PSIK mayoritas berjenis kelamin perempuan dengan motivasi tinggi dan sedang memperoleh IPK kategori dengan pujian, masing-masing sebesar 59,4%, 93,1% dan 83,3%. Mahasiswa PSPD, PSPDG, dan PSIK berusia 17-18 tahun memiliki motivasi tinggi dan sedang memperoleh IPK kategori dengan pujian masing-masing sebesar 83,3%, 79,3%, 93,13%. Mahasiswa PSPDG dan PSIK yang berasal dari Sulut dengan motivasi sedang dan tinggi memperoleh nilai IPK dengan pujian masing-masing sebesar 58,6% dan 84,3%, sedangkan mahasiswa PSPD yang berasal dari luar Sulut sebesar 60,4% Simpulan: Penelitian menunjukan mahasiswa PSPD, PSPDG, dan PSIK memiliki motivasi tinggi dan sedang dominan, berjenis kelamin perempuan, dan memperoleh IPK kategori dengan pujian. Kemudian, mahasiswa PSPDG dan PSIK asal Sulut dengan motivasi sedang dan tinggi cenderung meraih IPK dengan kategori “dengan pujian,” dengan begitu pula mahasiswa PSPD yang berasal dari luar Sulut. Kata kunci: Motivasi; Indeks Prestasi Kumulatif, Jenis Kelamin, Usia, Asal